From Tradition to Transition: A Multidimensional Analysis of Household Dietary Sustainability in Uganda - Asiimwe, Robert; Donkor, Emmanuel; Keding, Gudrun; Sekabira, Haruna; Danquah, Ina; Bhatt, Mahir; Teuber, Ramona; Justus Liebig University Giessen (My University, 2026)
This dataset contains harmonized repeated cross-sectional household survey data from Uganda covering the period 2005–2019. The data were compiled from nationally representative household consumption and expenditure surveys and used to examine temporal patterns and socioeconomic associations in dietary sustainability among Ugandan households. Variables include household food consumption, food expenditure, dietary diversity indicators, ultra-processed food expenditure shares, diet-related greenhouse gas emissions (CO₂e), and household demographic and socioeconomic characteristics. The dataset was cleaned and harmonized to ensure comparability across survey waves and supports analysis of the nutritional, environmental, and economic dimensions of dietary sustainability. The dataset was created with Stata.
Keywords: Sustainable food systems; sustainable diet index, Uganda, household food consumption, food affordability, dietary trends; ddc:300; ddc:500